2004
DOI: 10.1111/j.1601-5223.1995.00163.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Phenotypic Variation and Climatic Factors at Collecting Sites in Durum Wheat Landraces

Abstract: Information on the relationships between climatic features at collecting sites and morpho-physiological variation of genetic resources could enhance the understanding of evolutive adaptation patterns and assist germplasm collectors and users. In the present study, such relationships were investigated in durum wheat landraces of four countries of origin, viz. Ethiopia, Morocco, Syria, and Turkey, evaluated in northern Syria. Several relationships were found which mainly concerned drought stress and high tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 11 publications
4
9
0
Order By: Relevance
“…Early flowering is one of the most common physiological mechanisms for escaping drought. The presence in eastern genotypes of a high frequency of alleles reducing time to flowering (89%) is in agreement with previous studies showing that drought stress and high temperature in the collecting site of durum wheat landraces reduced cycle length (Annicchiarico et al, 1995 ). Solar radiation has been reported to be one of the climatic variables most affecting the cycle length of landraces, with those from areas with high solar radiation having the shortest one (Royo et al, 2014 ).…”
Section: Discussionsupporting
confidence: 92%
“…Early flowering is one of the most common physiological mechanisms for escaping drought. The presence in eastern genotypes of a high frequency of alleles reducing time to flowering (89%) is in agreement with previous studies showing that drought stress and high temperature in the collecting site of durum wheat landraces reduced cycle length (Annicchiarico et al, 1995 ). Solar radiation has been reported to be one of the climatic variables most affecting the cycle length of landraces, with those from areas with high solar radiation having the shortest one (Royo et al, 2014 ).…”
Section: Discussionsupporting
confidence: 92%
“…The cooler climate of the Balkan Peninsula may have resulted in a lengthening of the growth cycle of the landraces that originated in this area [ 25 ]. On the other hand, the high temperatures and low rainfall of the southeastern Mediterranean Basin may have reduced time to heading [ 25 , 54 ] as an adaptive physiological mechanism for terminal drought escape.…”
Section: Discussionmentioning
confidence: 99%
“…The observed cycle lengthening of the landraces from cool Tmin average minimum daily temperature, Tmax average maximum daily temperature, Rad average daily solar radiation, Rh average daily relative humidity, ET 0 accumulated potential evapotranspiration, Rain average daily rainfall, CDW crop dry weight areas in comparison with those of warm ones is consistent with the reported enhanced crop growth period induced in wheat by lower mean temperatures during the growing period (Chakrabarti et al 2011). A previous study showed that drought stress and high temperature in the collecting site of durum wheat landraces affected drought tolerance and reduced time to heading thus affecting yield potential (Annicchiarico et al 1995). Early heading is one of the most common physiological mechanisms of drought escape.…”
Section: Discussionmentioning
confidence: 99%